Volume 2A: Turbomachinery 2019
DOI: 10.1115/gt2019-90150
|View full text |Cite
|
Sign up to set email alerts
|

Loss in Axial Compressor Bleed Systems

Abstract: Loss in axial compressor bleed systems is quantified, and the loss mechanisms identified, in order to determine how efficiency can be improved. For a given bleed air pressure requirement, reducing bleed system loss allows air to be bled from further upstream in the compressor, with benefits for the thermodynamic cycle. A definition of isentropic efficiency which includes bleed flow is used to account for this. Two cases with similar bleed systems are studied: a low-speed, single-stage research compressor and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Grimshaw et al [13] studied the loss mechanism in the bleed system and concluded that there are two main sources of losses therein: (i) the shear stresses generated between the high-speed jet and the slot wall and (ii) the viscous mixing between the jet and the low-speed fluid in the plenum chamber. Gomes et al [14] investigated how different off-take duct arrangements affect the flow in the bleed system, including double and quadruple distributions, and the choice of arrangement has a strong effect on the circumferential flow pattern in the plenum chamber.…”
Section: Introductionmentioning
confidence: 99%
“…Grimshaw et al [13] studied the loss mechanism in the bleed system and concluded that there are two main sources of losses therein: (i) the shear stresses generated between the high-speed jet and the slot wall and (ii) the viscous mixing between the jet and the low-speed fluid in the plenum chamber. Gomes et al [14] investigated how different off-take duct arrangements affect the flow in the bleed system, including double and quadruple distributions, and the choice of arrangement has a strong effect on the circumferential flow pattern in the plenum chamber.…”
Section: Introductionmentioning
confidence: 99%